Association of Tumor Size With Myometrial Invasion, Lymphovascular Space Invasion, Lymph Node Metastasis, and Recurrence in Endometrial Cancer: A Meta-Analysis of 40 Studies With 53,276 Patients - Jin, Xiaoying; Shen, Chunjuan; Yang, Xiaodi; Yu, Yayuan; Wang, Jianzhang; Che, Xuan (Frontiers in Oncology, 2022)
Background: Tumor size has been suggested to correlate to clinicopathological characteristics and overall survival in endometrial cancer. However, the relationship between tumor size and myometrial invasion (MI), lymphovascular space invasion (LVSI), lymph node metastasis (LNM), recurrence and overall survival (OS) remains controversial and no meta-analysis has been conducted. Therefore, a systematic review and meta-analysis was performed to discuss this issue. Methods: Relevant articles were collected from PubMed, EMBASE and Cochrane Library databases from January 1990 to June 2021. We identified studies reporting the cut-off of 20mm with tumor size in endometrial cancer. The endpoints included MI, LVSI, LNM, recurrence and OS. Data were pooled for meta-analysis using Review Manager 5.1. Additionally, odds ratios (ORs), cumulative analyses of hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs) were conducted. Results: A total of 40 articles with 53276 endometrial cancer patients were included in the meta-analysis. It contained 7 articles for MI, 6 for LVSI, 21 for LNM, 7 for recurrence and 3 for OS. Primary tumor size > 20mm was significantly associated with deep of myometrial invasion (OR = 5.59, 95 % CI [5.02-6.23], p<0.00001), positive LVSI (OR=3.35, 95 % CI [2.34, 4.78], p<0.00001), positive lymph node metastasis (LNM) (OR=4.09, 95 % CI [3.60,4.63], p<0.00001) and recurrence (OR=3.52, 95 % CI [2.39,5.19], p<0.00001). Tumor size was also related with OS via meta-synthesis of HRs in univariate survival (HR 2.13, 95% CI 1.28–3.53, P=0.003). There was no significant publication bias in this study by funnel plot analysis. Conclusion: Primary tumor size>20mm was an independent predictive factor for the deepth of myometrial invasion, positive lymphovascular space invasion, positive lymph node metastasis, recurrence and poor overall survival. Well-designed and multi-center studies with a larger sample size are still required to verify the findings.